MiR-155 and miR-484 Are Associated with Time to Progression in Metastatic Renal Cell Carcinoma Treated with Sunitinib. (3rd May 2015) - Merhautova, Jana; Hezova, Renata; Poprach, Alexandr; Kovarikova, Alena; Radova, Lenka; Svoboda, Marek; Vyzula, Rostislav; Demlova, Regina; Slaby, Ondrej
Abstract : Background . Sunitinib is a tyrosine kinase inhibitor used in the treatment of metastatic renal cell carcinoma. The main difficulty related to the treatment is the development of drug resistance followed by rapid progression of the disease. We analyzed tumor tissue of sunitinib treated patients in order to find miRNAs associated with therapeutic response. Methods . A total of 79 patients with metastatic renal cell carcinoma were included in our study. miRNA profiling in tumor tissue samples was performed by TaqMan Low Density Arrays and a group of selected miRNAs (miR-155, miR-374-5p, miR-324-3p, miR-484, miR-302c, and miR-888) was further validated by qRT-PCR. Normalized data were subjected to ROC and Kaplan-Meier analysis. Results . We reported decreased tissue levels of miR-155 and miR-484 as significantly associated with increased time to progression (miR-155: median TTP 5.8 versus 12.8 months, miR-484: median TTP 5.8 versus 8.9 months). Conclusion . miR-155 and miR-484 are potentially connected with sunitinib resistance and failure of the therapy. miR-155 is a known oncogene with direct influence on neovascularization. Biological role of miR-484 has to be clarified. Stratification of patients based on miRNA analysis would allow more personalized approach in therapy of metastatic renal cell carcinoma.